2021
DOI: 10.1097/corr.0000000000001775
|View full text |Cite
|
Sign up to set email alerts
|

Telemedicine Use in Orthopaedic Surgery Varies by Race, Ethnicity, Primary Language, and Insurance Status

Abstract: Background Healthcare disparities are well documented across multiple subspecialties in orthopaedics. The widespread implementation of telemedicine risks worsening these disparities if not carefully executed, despite original assumptions that telemedicine improves overall access to care. Telemedicine also poses unique challenges such as potential language or technological barriers that may alter previously described patterns in orthopaedic disparities. Questions/pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
63
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 61 publications
(65 citation statements)
references
References 26 publications
1
63
1
Order By: Relevance
“…Telehealth usage has exponentially increased during the COVID-19 pandemic, introducing new disparities in appointment access with Hispanic/ Latinx, Asian, non-English speaking patients, and patients insured through Medicaid having lower access to telehealth orthopaedic appointments than other patients. 33,53 A similar effect exists with electronic patient portal usage within orthopaedic settings. While such portals decrease no-show rates and increase patient satisfaction with their care, they have had lower utilization among patients with lower levels of education, those who are non-English speaking, and those who are African American or Hispanic.…”
Section: Scheduling Telehealth and Virtual Patient Portalsmentioning
confidence: 88%
See 2 more Smart Citations
“…Telehealth usage has exponentially increased during the COVID-19 pandemic, introducing new disparities in appointment access with Hispanic/ Latinx, Asian, non-English speaking patients, and patients insured through Medicaid having lower access to telehealth orthopaedic appointments than other patients. 33,53 A similar effect exists with electronic patient portal usage within orthopaedic settings. While such portals decrease no-show rates and increase patient satisfaction with their care, they have had lower utilization among patients with lower levels of education, those who are non-English speaking, and those who are African American or Hispanic.…”
Section: Scheduling Telehealth and Virtual Patient Portalsmentioning
confidence: 88%
“…30,31 Utilizing non-certified interpreters contributes to LEP patients/families facing decreased access to telehealth appointments, lower comprehension of orthopaedic terminology and treatments, and lower interpersonal satisfaction with the care that they receive. 26,27,32,33 The adult literature further demonstrates resultant disparities in quality of care and postoperative outcomes among non-English speaking patients. 6…”
Section: Languagementioning
confidence: 99%
See 1 more Smart Citation
“…While several authors have demonstrated that patients from disadvantaged sociodemographic backgrounds have diminished access to spine care, [20][21][22][23] comparatively little work has been done on the implications of these barriers on symptoms at baseline and decisions for treatment at initial presentation. Moreover, attempts to rigorously characterize these differences have proved inconclusive due to the heterogeneity and lack of available data.…”
Section: Discussionmentioning
confidence: 99%
“…The interactions between ethnicity, socio-economic status, and digital/health literacy are multifaceted and complex [ 3 , 4 ] but the data generally demonstrate that significant disparities exist that disproportionately affect minority and lower socio-economic groups [5] , [6] , [7] . While one can argue these challenges are not exclusive to any single specialty[ 8 , 9 ], CF teams would do well to consider how best to tailor systems to improve outcomes for people with CF [10] .…”
mentioning
confidence: 99%